Long-term trends in cancer mortality in the Republic of Moldova (One Health & Risk Management, 2021)
Introduction. Cancer is the second cause-of-death mortality pattern in the Republic of Moldova. The study of both cancer mortality by age and its detailed causes is an important tool for evidence-based public health policy. The study aims at comparing recent changes in cancer mortality with long-term trends, depending on specific causes and age. Material and methods. This study was carried out on the reconstructed 1965-2018 death time series, according to the 10th revision of the International Classification of Diseases. Standardized death rates were computed.  Results. After a gradual increase in the ‘70s and ‘80s of the last century, cancer mortality rate showed “reversed” patterns and started to decline in the ‘90s.  This decline was due to the data quality issue and to the competing risks of dying from other causes sensitive to the social and economic circumstances of the ‘90s. Since the beginning of the millennium, cancer mortality has resumed its growth that continues up to now. Despite the increasing overall trend in cancer mortality rate during 1965-2018, the analysis by age and specific causes revealed opposite trends.  Conclusions. The malignant neoplasms specific for certain sites and age groups (stomach, uterus, leukaemia in children) showed, however some therapeutic progress, while the situation for other tumour sites (lung, breast, and intestine) worsened significantly. The moderate decrease in lung cancer in the 1990s should be cautiously interpreted.